Perlindungan Hukum Hak Kekayaan Intelektual Bagi Produk Kreatif Usaha Kecil Menengah Di Yogyakarta - Dyah Permata Budi Asri (Jurnal Hukum IUS QUIA IUSTUM, 2020)
There is a rather large presence of Small and Medium Enterprises (SMEs) as part of creative industry in Yogyakarta, yet the Intellectual Property Rights management is still very minimum. The problems in this study are, first, why the protection of Intellectual Property Rights is important for small and medium business entities as creative industries in the Special Region of Yogyakarta. Second, how is the role of the regional government of the Special Region of Yogyakarta in order to provide legal protection for Intellectual Property Rights to small and medium businesses in the special Region of Region Yogyakarta. This paper applies a juridical-empirical approach by using primary data. This study concludes that firstly, the potential market for creative industries has a tendency to develop continuously, since SMEs in Yogyakarta contribute 59% of Gross Domestic Revenue in Special Region of Yogyakarta hence the protection of IPRs on creative economic products to guarantee the economic rights of the creators is crucial. Secondly, the role of local governments at the moment in the context of providing IPR protection for SMEs is carried out by establishing an Intellectual Property Management Center (BPKI), and developing a website to provide IPR services, namely "JogjaKI".